Becoming bilingual : language acquisition in a bilingual community - Lyon, Jean, 1939- (Bilingual education and bilingualism ;, 1996)
Lyon explores the processes of monolingual and bilingual language development in preschool children. She provides an overview of child bilingualism, then looks at the factors which predict the language use of the child.